Autologous Mesenchymal Stem Cells Produce Concordant Improvements in Regional Function, Tissue Perfusion, and Fibrotic Burden When Administered to Patients Undergoing Coronary Artery Bypass Grafting: The Prospective Randomized Study of Mesenchymal Stem Cell Therapy in Patients Undergoing Cardiac Surgery (PROMETHEUS) Trial - Karantalis, Vasileios; DiFede, Darcy L.; Gerstenblith, Gary; Pham, Si; Symes, James; Zambrano, Juan Pablo; Fishman, Joel; Pattany, Pradip; McNiece, Ian; Conte, John; Schulman, Steven; Wu, Katherine; et al. (Circulation research, 2014)
RATIONALE:Although accumulating data support the efficacy of intramyocardial cell-based therapy to improve left ventricular (LV) function in patients with chronic ischemic cardiomyopathy undergoing CABG, the underlying mechanism and impact of cell injection site remain controversial. Mesenchymal stem cells (MSCs) improve LV structure and function through several effects including reducing fibrosis, neoangiogenesis, and neomyogenesis. OBJECTIVE:To test the hypothesis that the impact on cardiac structure and function after intramyocardial injections of autologous MSCs results from a concordance of prorecovery phenotypic effects. METHODS AND RESULTS:Six patients were injected with autologous MSCs into akinetic/hypokinetic myocardial territories not receiving bypass graft for clinical reasons. MRI was used to measure scar, perfusion, wall thickness, and contractility at baseline, at 3, 6, and 18 months and to compare structural and functional recovery in regions that received MSC injections alone, revascularization alone, or neither. A composite score of MRI variables was used to assess concordance of antifibrotic effects, perfusion, and contraction at different regions. After 18 months, subjects receiving MSCs exhibited increased LV ejection fraction (+9.4±1.7%, P=0.0002) and decreased scar mass (−47.5±8.1%; P<0.0001) compared with baseline. MSC-injected segments had concordant reduction in scar size, perfusion, and contractile improvement (concordant score2.93±0.07), whereas revascularized (0.5±0.21) and nontreated segments (−0.07±0.34) demonstrated nonconcordant changes (P<0.0001 versus injected segments). CONCLUSIONS:Intramyocardial injection of autologous MSCs into akinetic yet nonrevascularized segments produces comprehensive regional functional restitution, which in turn drives improvement in global LV function. These findings, although inconclusive because of lack of placebo group, have important therapeutic and mechanistic hypothesis-generating implications. CLINICAL TRIAL REGISTRATION:URLhttp://clinicaltrials.gov/show/NCT00587990. Unique identifierNCT00587990.